Midbrain and Hindbrain Involvement in Lissencephaly - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Involvement of the midbrain and hindbrain (MHB) in the various groups of lissencephalies was examined in an MRI study of 111 patients (aged 1 day to 32 years; mean 5 years 4 months) studied at University of California San Francisco, and centers in France, Belgium, and Turkey.